New targets of morphine postconditioning protection of the myocardium in ischemia/reperfusion injury: Involvement of HSP90/Akt and C5a/NF-κB - Tu Rong-Hui (De Gruyter, 2021)
Activation of the complement component 5a (C5a) and nuclear factor κB (NF-κB) signaling is an important feature of myocardial ischemia/reperfusion (I/R) injury and recent studies show that morphine postconditioning (MP) attenuates the myocardial injury. However, the mediating cardioprotective mechanisms remain unclear. The present study explores the role and interaction of heat shock protein 90 (HSP90), Akt, C5a, and NF-κB in MP-induced cardioprotection.